Architect's duties in relation to supervision of construction projects - Sharisa Hussein, 1986-; Maizon Hashim, supervisor; Fakulti Alam Bina (2013)
Thesis (Sarjana Sains (Pengurusan Kontrak Pembinaan)) - Universiti Teknologi Malaysia, 2013